The platform will undergo maintenance on Sep 14 at about 9:30 AM EST and will be unavailable for approximately 1 hour.
2014
DOI: 10.1128/jvi.02372-13
|View full text |Cite
|
Sign up to set email alerts
|

Adenovirus E1B 19-Kilodalton Protein Modulates Innate Immunity through Apoptotic Mimicry

Abstract: Cells that undergo apoptosis in response to innate immune inflammation during accumulation of virally infected cells at sites of infection and suggest that E1B 19K-deleted, replicating adenoviral vectors might induce greater inflammatory responses to virally infected cells than E1B 19K-positive vectors, because of the net effect of their loss-of-function mutation. IMPORTANCE We observed that cells dying a nonapoptotic cell death induced by adenovirus infection repressed macrophage proinflammatory responses whi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
26
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 21 publications
(26 citation statements)
references
References 41 publications
0
26
0
Order By: Relevance
“…65 That is, apoptotic-like cells, dying as a result of infection with an E1B 19 K-deficient adenovirus, were not immunosuppressive, and non-apoptotic cells, dying as a result of wild-type adenoviral infection, were immunosuppressive. This 'reversed' behavior was attributable genetically to E1B 19 K. That authentic Bcl-2 could substitute for E1B 19 K, but that it does not program such a reversed behavior in the context of Figure 3 Glycosomal localization of glycolytic enzymes.…”
Section: Reprogrammed Cell Deathmentioning
confidence: 99%
See 1 more Smart Citation
“…65 That is, apoptotic-like cells, dying as a result of infection with an E1B 19 K-deficient adenovirus, were not immunosuppressive, and non-apoptotic cells, dying as a result of wild-type adenoviral infection, were immunosuppressive. This 'reversed' behavior was attributable genetically to E1B 19 K. That authentic Bcl-2 could substitute for E1B 19 K, but that it does not program such a reversed behavior in the context of Figure 3 Glycosomal localization of glycolytic enzymes.…”
Section: Reprogrammed Cell Deathmentioning
confidence: 99%
“…65 The complete genetic basis of adenoviral cell death reprogramming and its mechanism remain to be elucidated. Similarly, whether other viruses direct cell death reprogramming remains unexplored.…”
Section: Reprogrammed Cell Deathmentioning
confidence: 99%
“…We reported that Ad5 E1B 19K function is required for Ad-infected, dying cells (CPE corpses) to repress stimulus-induced, NF-B-dependent transcription and related cytokine production by responder macrophages, an E1B 19K function termed apoptotic mimicry (7). As observed with wt Ad5 infection, wt Ad14-infected human A549 (lung epithelial cell) CPE corpses repressed PMA-induced NF-B-dependent transcription in reporter cells, whereas CPE corpses infected with either Ad14p1 clinical isolate failed to repress this response, in a pattern similar to that of infection with the 19K-deleted Ad mutant, H5 dl337 (Fig.…”
Section: Ad14p1 Isolates Exhibit Large-plaque and Cytocidal Phenotypesmentioning
confidence: 99%
“…We have previously reported that cells dying as a result of wt Ad5 infection repress the host inflammatory response to the virus (7). Expression of the Ad E1B 19-kilodalton (19K) protein is required for this anti-inflammatory activity since cells infected with an Ad mutant that lacks expression of 19K fail to exhibit anti-inflammatory activity.…”
mentioning
confidence: 99%
See 1 more Smart Citation